An open-styled dielectric-lined azimuthally periodic circular waveguide for a millimeter wave traveling-wave tube - 刘漾 魏彦玉 徐进 殷海荣 岳玲娜 宫玉彬 王文祥 (Chinese physics B, 2012)
An open-styled dielectric-lined azimuthMly periodic circular waveguide （ODLAP-CW） for a millimeter-wave traveling-wave tube （TWT） is proposed, which is a modified form of a dielectric-lined azimuthally periodic circular waveguide （DLAP-CW）. The slow-wave characteristics of the open-styled DLAP-CW are studied by using the spatial harmonics method, which includes normalized phase velocity and interaction impedance. The complicated dispersion equations are numerically solved with MATLAB and the results are in good agreement with the simulation results obtained from HFSS. The influence of structural parameters on the RF properties is investigated based on our theory. The numerical results show that the optimal thickness of the metal rod can increase the interaction impedance, with the dielectric constant held fixed. Finally, the slow-wave characteristics and transmission properties of an open-styled structure are compared with those of the DLAP-CW. The results validate that the mode competition is eliminated in the improved structure with only a slight influence on the dispersion characteristics, which may significantly improve the stability of an open-styled DLAP-CW-based TWT, and the interaction efficiency is also improved.